A tomographic-PIV investigation of vapor-induced flow structures in confined jet impingement boiling. (September 2016) - Rau, Matthew J.; Vlachos, Pavlos P.; Garimella, Suresh V.
Abstract: Tomographic particle image velocimetry (PIV) is used to study the effect of confinement gap height on the liquid flow characteristics in jet impingement boiling. This first application of tomographic PIV to flow boiling is significant given the complexity of confined two-phase jet impingement. A jet of subcooled water at a Reynolds number of 5, 000 impinges onto a circular heat source undergoing boiling heat transfer at a constant heat input. Confinement gap heights of 8, 4, and 2 jet diameters are investigated. A visual hull method is used to reconstruct the time-varying regions of the vapor in the flow. The vapor motion is found to govern the liquid flow pattern and turbulence generation in the confinement gap. Time-averaged velocities and regions of turbulent kinetic energy in the liquid are highest for a confinement gap height of 8 jet diameters, with lower velocity magnitude and turbulence being observed for the smaller spacings. Coherent vortical structures identified with the λ2 -criterion are found to occur most frequently near the moving vapor interface. The most intense regions of turbulent kinetic energy do not coincide with the location of coherent structures within the flow. Irrotational velocity fluctuations in the liquid phase caused by vapor bubble pinch-off are the primary cause of the high turbulent kinetic energy measured in these regions. At a gap height of H / d  = 2 the vapor plume is constrained as it grows from the heat source, causing bulk flow oscillations in the downstream region of the confinement gap. Graphical abstract: